LANDASAN ILMIAH ILMU INFORMASI PERPUSTAKAAN DALAM PERSPEKTIF ILMU KOMUNIKASI - Rohanda, Rohanda (Jurnal Kajian Informasi dan Perpustakaan, 2013)
The core issues that are discussed in this article is the concept, the philosophical foundation and the scientific basis Information and Library Studies in a variety of perspectives. Given the information and library science is so broad, comprehensive and interdisciplinary so confusing in the placement or provision of address and its container in a particular field of science clumps. Does it make clumps of Humanities, Social Communication, Technology or to a group of Science and Mathematics. Then, whether stand-alone or as an interdisciplinary science. There are no definitive answers. Information and Library Science is formulated as a concept of interdisciplinary remember that science in the division of the classification of DDC, enter the group General Science (general science), meaning that knowledge can stand as a discipline itself, did not join the other sciences as a subdivision from other fields, so that with this paper designed and introduced scientific basis as well as notify a clear address of the place of the art. The new paradigm of Information and Library Science is a science that is stable like modern science are not looking at the world of work alone, but more towards the development of problem-solving strategies that are so extensive and complicated. As a unit of knowledge, information and library science should be independent, not attached or affixed to other disciplines.Inti persoalan yang dibahas dalam artikel ini adalah konsep, landasan filosofis dan landasan ilmiah Ilmu Informasi dan Perpustakaan dalam berbagai perspektif. Mengingat Ilmu Informasi dan Perpustakaan begitu luas, komprehensif dan interdisiplin sehingga membingungkan dalam penempatan atau pemberian alamat dan wadahnya di bidang rumpun ilmu tertentu. Apakah masuk rumpun Ilmu Budaya, Sosial, Komunikasi, Teknologi atau pada kelompok Sains dan Matematika. Kemudian, apakah berdiri sendiri atau sebagai ilmu interdisiplin. Belum ada jawaban yang pasti. Ilmu Informasi dan Perpustakaan diformulasikan sebagai konsep interdisiplin mengingat ilmu tersebut dalam pembagian klasifikasi DDC, masuk pada kelompok General Science (ilmu pengetahuan umum), artinya ilmu tersebut dapat berdiri sebagai disiplin ilmu sendiri, tidak bergabung dengan ilmu lain sebagai sub divisi dari bidang lain, sehingga dengan tulisan ini dirancang dan diperkenalkan landasan ilmiah yang sekaligus memberitahukan alamat yang jelas tentang kedudukan ilmu tersebut. Paradigma baru Ilmu Informasi dan Perpustakaan merupakan ilmu yang stabil layaknya ilmu modern yang tidak lagi memandang dunia kerja saja, akan tetapi lebih ke arah pengembangan strategi pemecahan masalah yang begitu luas dan rumit. Sebagai satu kesatuan ilmu, Ilmu Informasi dan Perpustakaan sudah seharusnya mandiri, tidak menempel atau ditempelkan pada bidang ilmu lain.